2011
DOI: 10.1002/ccd.23392
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus‐ versus paclitaxel‐eluting stents for coronary bifurcations intervention

Abstract: Compared with PES, SES reduced the incidence of TLR, main-branch restenosis and MACE in coronary bifurcation intervention, while the risk of stent thrombosis was similar between SES and PES groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…21 Indeed, preliminary results with the BiOSS Expert LIM stent as well as studies using other platforms have suggested that sirolimus-eluting stents may be more effective than paclitaxel-eluting ones. 22,23 Moreover, BiOSS Expert stents are made of stainless steel and therefore have relatively thick struts (naked, 120 mm), which might predispose to excessive neointimal proliferation. The use of a cobaltchromium alloy allows for thinner stent struts (60-90 mm), which may result in lower LLL.…”
Section: Discussionmentioning
confidence: 99%
“…21 Indeed, preliminary results with the BiOSS Expert LIM stent as well as studies using other platforms have suggested that sirolimus-eluting stents may be more effective than paclitaxel-eluting ones. 22,23 Moreover, BiOSS Expert stents are made of stainless steel and therefore have relatively thick struts (naked, 120 mm), which might predispose to excessive neointimal proliferation. The use of a cobaltchromium alloy allows for thinner stent struts (60-90 mm), which may result in lower LLL.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the BiOSS Expert Registry evaluating the BiOSS paclitaxel-eluting stent were encouraging and, subsequently, the randomised POLBOS I trial comparing BiOSS Expert with rDES was conducted 3,12 . However, in the meantime many studies have shown paclitaxel-eluting stents to be inferior to "olimus"-eluting stents 13 . Therefore, a new version of the BiOSS stent, the BiOSS LIM, eluting sirolimus, was designed.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 years of follow-up in PES group the rate of MACE was 28.6 % and in SES 10.6 % (P = 0.03), whereas the LLL was 1.03 ± 0.45 and 0.28 ± 0.54 mm (P < 0.001) respectively. Also, in a meta-analysis it was proved that when comparing with PES, SES reduced the incidence of TLR, main-branch restenosis and MACE in coronary bifurcation intervention, while the risk of stent thrombosis was similar between SES and PES groups [ 15 ].…”
Section: Discussionmentioning
confidence: 99%